The older the better? Are younger Norwegian adults losing ground on basic numeracy skills? - Billington, Mary G.; Gabrielsen, Egil (NOMAD Nordic Studies in Mathematics Education, 2017)
Results from the OECD survey of adult skills, 2012 brought good tidings for Norway. The average numeracy score for the Norwegian adult population lies well over the OECD average. However, a closer look at the age skill profile shows that while older Norwegians score well over the OECD average for their age group, younger Norwegians score around the OECD average. Comparing these results to results from an earlier study of adult skills, conducted in 2003, suggests a downward trend in numeracy proficiency for the younger generation. We discuss recent school reforms as a possible cohort effect influencing this trend.